Форми транскордонного співробітництва в практиці європейських держав - Митко, Антоніна Миколаївна; Mytko, Antonina M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
The article analyzes the theoretical and methodological foundations of the study of the concept of cross-border cooperation. The features of its elements and characterized the ground for information support and provision of CBC.
Cross-border cooperation in the practice of European States
А. М.Митко, к. політ. н., доц. кафедри міжнародної інформації Східноєвропейського національного університету імені Лесі Українки (Україна, м. Луцьк)
Keywords: cross-border cooperation; forms CBC Euroregions